The impact of tongue dimension on air volume in brachycephalic dogs. Issue 3 (30th July 2019) - Jones, Brittani A.; Stanley, Bryden J.; Nelson, Nathan C.
Abstract: Objective: To compare the dimensions and density of the tongue in brachycephalic and mesaticephalic dog breeds and to document the relative extents of the nasopharyngeal and oropharyngeal airways occupied by the tongue and palatal tissues. Study design: Case control study. Animals: Sixteen brachycephalic dogs and 12 mesaticephalic dogs. Methods: The volume of the tongue was measured with computed tomography in all dogs. Cross‐sectional areas of tongue, oropharynx, nasopharynx, and palatal soft tissue were evaluated at two levels, the caudal aspect of the hard palate and the level of the hamulae of the pterygoid. Density of the tongue and soft palate were measured. All variables were compared between brachycephalic and mesaticephalic dogs ( P ≤ .05). Results: Absolute tongue volumes did not differ between groups, the volume of the tongue was greater in brachycephalic dogs than in mesaticephalic dogs when expressed relative to (a) body weight (median 5650, interquartile range [IQR] 4833‐6522 vs median 4454, IQR 4309‐4743, respectively), (b) ratio between skull length/width (70 833, IQR 62490‐126 209 vs 48 064, IQR 22984‐64 279, respectively), and (c) skull length (689.93, IQR 618.55‐970.61 vs 460.04, IQR 288.77‐561.69, respectively). The proportion of air (oropharyngeal and nasopharyngeal)/soft tissue (tongue and palatal tissue) in brachycephalic dogs was decreased by approximately 60%, and the tongue was approximately 10 times denser in brachycephalic dogs than in mesaticephalic dogs. Conclusion: A relative macroglossia was detected in brachycephalic dogs along with reduced air volume in the upper airway. Tongues of brachycephalic dogs were denser than those of mesaticephalic dogs. Clinical significance: The relative macroglossia in brachycephalic breeds may contribute to upper airway obstruction.